Analysis of Sweet cherry (Prunus avium L.) Leaves for Plant Signal Molecules That Activate the syrB Gene Required for Synthesis of the Phytotoxin, Syringomycin, by Pseudomonas syringae pv syringae. - Mo, Y. Y. (1995)
An important aspect of the interaction of Pseudomonas syringae pv syringae with plant hosts is the perception of plant signal molecules that regulate expression of genes, such as syrB, required for synthesis of the phytotoxin, syringomycin. In this study, the leaves of sweet cherry (Prunus avium L.) were analyzed to determine the nature of the syrB-inducing activity associated with tissues of a susceptible host. Crude leaf extracts yielded high amounts of total signal activity of more than 12,000 units g-1 (fresh weight) based on activation of a syrB-lacZ fusion in strain B3AR132. The signal activity was fractionated by C18 reversed-phase high-performance liquid chromatography and found to be composed of phenolic glycosides, which were resolved in three regions of the high-performance liquid chromatography profile, and sugars, which eluted with the void volume. Two flavonol glycosides, quercetin 3-rutinosyl-4[prime]-glucoside and kaempferol 3-rutinosyl-4[prime]-glucoside, and a flavanone glucoside, dihydrowogonin 7-glucoside, were identified. The flavonoid glycosides displayed similar specific signal activities and were comparable in signal activity to arbutin, a phenyl [beta]-glucoside, giving rise to between 120 and 160 units of [beta]-galactosidase activity at 10 [mu]M. Although D-fructose exhibits intrinsic low level syrB-inducing signal activity, D-fructose enhanced by about 10-fold the signal activities of the flavonoid glycosides at low concentrations (e.g. 10 [mu]M). This demonstrates that flavonoid glycosides, which represent a new class of phenolic plant signals sensed by P. s. syringae, are in sufficient quantities in the leaves of P. avium to activate phytotoxin synthesis.